Relationship of Omega-3 fatty acids DHA and EPA with the inflammatory biomarker hs-CRP in children with sickle cell anemia - Setty, B N Yamaja; Betal, Suhita Gayen; Miller, Robin E; Brown, Dawn S; Meier, Maureen; Cahill, Michele; Lerner, Norma B; Apollonsky, Nataly; Stuart, Marie J (Prostaglandins, leukotrienes and essential fatty acids, 2019)
•Chronic inflammation is one of the hallmarks of sickle cell disease (SCD). We have previously demonstrated that the inflammatory biomarker hs-CRP positively correlated with vaso-occlusive pain in SCD.•In children with SCD, ratios of pro-inflammatory arachidonic acid (AA) to anti-inflammatory docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids are increased in red cell phospholipids due to a relative decrease in omega-3 fatty acids.•A relative deficiency of DHA and EPA correlates positively with hs-CRP in children with SCD.•A relative deficiency of DHA and EPA increases with age in children with SCD. Inflammation and vaso-occlusion play key roles in Sickle Cell Disease (SCD) pathophysiology. Lipoxygenase products of the omega-3 fatty acids (O3FAs), docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids, are potent anti-inflammatory mediators modulating pain. O3FAs decrease episodes of vaso-occlusion in SCD. We assessed erythrocyte fatty acid composition in two major cell membrane phospholipids, phosphatidylcholine and phosphatidylethanolamine, in children with SCD HbSS-disease (n = 38) and age/race-matched HbAA-controls (n = 18). Ratio of pro-inflammatory arachidonic acid (AA) to anti-inflammatory DHA and EPA (FA-Ratio), and its relationship to hs-CRP were evaluated. FA-Ratios were increased in both phosphatidylcholine and phosphatidylethanolamine in HbSS compared to controls. Correlations were noted in HbSS subjects between hs-CRP and FA-Ratios (p = 0.011). FA-Ratios increased with age (p = 0.0007) due to an increase in pro-inflammatory AA with a concomitant decrease in anti-inflammatory DHA. Findings demonstrate relative deficiencies in HbSS of the anti-inflammatory precursor fatty acids DHA and EPA, which correlates positively with hs-CRP.